Urinary Schistosomiasis Prevalence, Water Contact Activities, and Morbidity Indicators in Sankwala Community, Cross River, South-South Nigeria - Angbalaga, Gladys Abel; Akeh, Martins A; Anzene, Ablaku Asso; Ofem, Michael Gideon (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2024)
Urinary schistosomiasis is a predominant parasitic disease that is waterborne, ranking second behind malaria, especially among the rural populace, which is of public health significance in both tropical and subtropical regions of the world. This study aimed to determine the prevalence of urinary schistosomiasis, water contact activities, and morbidity indicators in Cross River, south-south Nigeria. Four locations were selected in the Sankwala community, and six hundred and twenty (620) participants were enrolled in the study using simple random sampling techniques. The prevalence rate was determined to be 37.06%. The test strip (combi 9) was used to determine the haematuria and proteinuria of the specimen. The results of participants whose activities or other engagements exposed them to contact with water ranged from 56.50% to 91.00%. Control measures involve the implementation of mass-targeted chemotherapy, the provision of adequate pipe-borne water, and health education in the studied community.